Antitumor Activity and Mechanism Study of Riluzole and Its Derivatives - Wu, Xiang-Long (Iran J Pharm Res, 2020)
To explore novel antitumor agents with high efficiency and low toxicity, riluzole alkyl derivatives (4a-4i) were synthesized. Their anti-proliferative activities against HeLa, HepG2, SP2/0, and MCF-7 cancer cell lines were assessed by the CCK-8 assay and compared with human normal liver (LO2) cells. Most of them showed potent cytotoxic effects against four human tumor cell lines and low toxic to LO2 cells. In particular, 2-(N-ethylamine)-6-trifluoromethoxy- benzothiazole (4a) showed a IC(50) value of 7.76 μmol/L in HeLa cells and was found to be nontoxic to LO2 cells up to 65 μmol/L. Furthermore, flow cytometry indicated that 4a could induce remarkable early apoptosis and G2/M cell cycle arrest in HeLa cells. It also impaired the migration ability of HeLa cells in wound healing assays. Western blot results demonstrated that 4a suppressed Bcl-2 protein expression but increased the level of Bax in HeLa cells, and elevated the Bax/Bcl-2 expression ratio. These new findings suggest that 4a exhibited beneficially anti-cervical cancer effect on HeLa cells by inducing HeLa cell apoptosis.